PEMODELAN DAN SIMULASI PROSES GASIFIKASI BATU BARA DALAM REAKTOR UNGGUN TERFLUIDISASI DENGAN REJIM GELEMBUNG - SYLVIANTI
Abstract : The optimal condition of coal gasification process can be determined through two ways. First, direct experiment in the process. It is difficult to be carried out for a preliminary research due to time consuming and high utilization of resources. And second, simulate the process using a model to interpret the real process. Through this way, high consumption for time and resources (money, chemicals/materials, and human resources) can be avoided. The objective of this research is to develop a model that can interpret the phenomena of coal gasification process in bubbling fluidized bed reactor, so that the optimal condition of the process can be determined. The optimal condition was characterized using two parameters, namely reactor efficiency (% conversion) and productivity (mass of product). The research was run by using Indonesian coal from Kaltim Prima Coal (KPC). The model takes into account several factors, which are mass and energy balances, fluid dynamics mechanism in two phases (bubbling-emulsion), and characteristics of gas-gas (homogeneous) and gas-solid (heterogeneous) reactions. System of 34 first order differential equations that generated derived from the mass and energy balances, are solved by the Runge-Kutta Methods through Matlab 6.5 version. Then, the model was verified using some experiment-based empirical evidences extracted from initial research of Chejne (2002). The model verification exhibits similar behavior and results to what Chejne has accomplished. The model was, then, simulated to determine the optimal condition. Variables used in this simulation are the rate of the feed, geometries of reactor, composition of devolatilisation product, and transport phenomena constants. The result of the simulation shows that reactor efficiency -interpreted by carbon, hydrogen, and thermal efficiency- are influenced by some variables. The reactor efficiency can be increased through (a) reducing tar concentration in devolatilisation product; (b) lowering steam-to-coal ratio; and (c) increasing height of bed in the reactor. If airto-coal ratio and temperature of feed gas increases, the carbon efficiency will increase. However, the increasing of these ratios will decrease the hydrogen efficiency. This model simulation is expected to help in determining of the optimal condition of the gasifier.